REPRESENTASI TOLERANSI BERAGAMA DALAM KONTEN DAN KOMENTAR LOG IN HABIB JA’FAR PADA KANAL YOUTUBE DEDDY CORBUZIER - Diaz Sari; Tsaniya Salsabilla; Nursalsabila Nursalsabila; Quratul Aqsha; Zeldi Firman (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2026)
In this ever-evolving digital era, the way we communicate has also changed, starting from utilizing media to exchange various information. This research discusses how religious tolerance is represented in the “Log In” program with Habib Ja'far on Deddy Corbuzier's YouTube channel with digital media as an intermediary, then how the audience responds through the comments column. The main objective of this research is to identify the representation of tolerance values in the video content and read the social dynamics reflected in the viewers' comments. The method used is a qualitative approach through content analysis and thematic coding of selected episodes and the comments that appear in the content. The results show that the program contains a strong message of tolerance through inclusive narratives, the use of non-confrontational language, and the selection of relevant and realistic topics in accordance with community conditions. On the other hand, audience comments showed supportive, reflective and controversial responses, indicating that the digital space can be a medium for active discussion of diversity issues. This suggests that social media such as YouTube play an important role in spreading tolerance values and encouraging direct public engagement. The findings enrich digital communication studies by highlighting the interplay between content and audience participation in shaping inclusive social discourse.